Associations of udder biometry with subclinical Mastitis in Gir crossbred cows - Shinde, A S; Mote, M G (Indian Journal of Dairy Science, 2021)
The investigation was undertaken on 110 Gir crossbred cows of different order of lactation and stage of lactation maintained at Research Cum Development Project on Cattle, MPKV, Rahuri. The overall least squares means of udder length, udder width, udder depth and udder circumference were 65.23 ± 1.45, 63.24 ± 1.45, 19.03 ± 0.51 and 86.49 ± 1.50 cm respectively. The least squares analysis of variance showed significant (P